Regulation of DNA-End resection by hnRNPU-like proteins promotes DNA double-strand break signaling and repair - Polo, Sophie E.; Kzhyshkowska, Julia (Molecular cell, 2012)
Summary: DNA double-strand break (DSB) signaling and repair are critical for cell viability, and rely on highly coordinated pathways whose molecular organization is still incompletely understood. Here, we show that heterogeneous nuclear ribonucleoprotein U-like (hnRNPUL) proteins 1 and 2 play key roles in cellular responses to DSBs. We identify human hnRNPUL1 and -2 as binding partners for the DSB sensor complex MRE11-RAD50-NBS1 (MRN) and demonstrate that hnRNPUL1 and -2 are recruited to DNA damage in an interdependent manner that requires MRN. Moreover, we show that hnRNPUL1 and -2 stimulate DNA-end resection and promote ATR-dependent signaling and DSB repair by homologous recombination, thereby contributing to cell survival upon exposure to DSB-inducing agents. Finally, we establish that hnRNPUL1 and -2 function downstream of MRN and CtBP-interacting protein (CtIP) to promote recruitment of the BLM helicase to DNA breaks. Collectively, these results provide insights into how mammalian cells respond to DSBs.